Handgrip Strength and Ideal Cardiovascular Health Among Colombian Children and Adolescents - Garcia-Hermoso, A (Mosby Inc., 2016)
Objective To evaluate the association between handgrip strength and ideal cardiovascular health (CVH) in Colombian children and adolescents. Study design During the 2014-2015 school years, we examined a cross-sectional component of the FUPRECOL (Association for Muscular Strength with Early Manifestation of Cardiovascular Disease Risk Factors among Colombian Children and Adolescents) study. Participants included 1199 (n = 627 boys) youths from Bogota (Colombia). Handgrip strength was measured with a standard adjustable hand held dynamometer and expressed relative to body mass (handgrip/body mass) and as absolute values in kilograms. Ideal CVH, as defined by the American Heart Association, was determined as meeting ideal levels of the following components: 4 behaviors (smoking status, body mass index, cardiorespiratory fitness, and diet) and 3 factors (total cholesterol, blood pressure, and glucose). Results Higher levels of handgrip strength (both absolute and relative values) were associated with a higher frequency of ideal CVH metrics in both sexes (P for trend ≤.001). Also, higher levels of handgrip strength were associated with a greater number of ideal health behaviors (P for trend <.001 in both boys and girls), and with a higher number of ideal health factors in boys (P for trend <.001). Finally, levels of handgrip strength were similar between ideal versus nonideal glucose or total cholesterol groups in girls. Conclusions Handgrip strength was strongly associated with ideal CVH in Colombian children and adolescents, and thus supports the relevance of early targeted interventions to promote strength adaptation and preservation as part of primordial prevention. © 2016 Elsevier Inc.